Surface Water Microplastics in the St. Lawrence River and Estuary in Canada - Valerie S. Langlois; Tuan Anh To; Eve Larocque; Julien Gigault; Raphael A. Lavoie (PLoS ONE, 2025)
Microplastics (MPs) are synthetic or semisynthetic polymers that are widely distributed throughout most ecosystems and have the potential to be harmful to living organisms. In this study, we assessed the MP fraction in the top 40 cm of surface water in response to varying salinity levels at 11 distinct sites across the St. Lawrence River and Estuary (SLRE). We employed two sampling nets of different mesh size to collect MPs (100 and 300 µm). These nets were simultaneously towed in parallel from a vessel during three separate sampling events at each designated site. Filtrates collected from these samples underwent analysis of plastic fibers, fragments and spheres utilizing Fourier Transform Infrared Spectroscopy (FTIR). Data unequivocally confirmed the presence of MPs at 100% of the sites sampled within the SLRE. The most abundant categories of MPs identified were the fibers, followed by fragments and spheres. The FTIR analysis revealed the predominant materials to be polyester, polyethylene, polypropylene, nylon, and polystyrene. Notably the findings also suggest MPs are more likely aggregating when salinity increases. This work offers valuable insights into the distribution and behavior of MPs contributing to the preservation and management of water resources.